Digital Dopamine and Modern Learning: Educational Technology Perspectives on Digital Content Addiction - Mokhamad Yaurizqika Hadi (EduTech Journal, 2026)
The proliferation of algorithmically curated digital content has introduced a neurological phenomenon increasingly referred to as "digital dopamine", the reward-loop mechanism by which engaging digital stimuli trigger repeated dopamine release, fostering habitual and addictive consumption patterns. This systematic literature review examines the intersection of this phenomenon with modern learning from the perspective of Educational Technology. Drawing on 20 peer-reviewed references published between 2021 and 2024, the study investigates how digital content addiction disrupts cognitive load, attention span, deep learning, and academic performance, while also exploring how Educational Technology practitioners can harness dopamine-driven design principles responsibly through gamification, adaptive learning, and AI-powered personalization. Results reveal that students with high digital content addiction exhibit significantly lower scores in deep learning (38% vs. 81%), attention span (45% vs. 78%), and academic performance (52% vs. 74%) compared to peers with low addiction profiles. Simultaneously, structured gamification and evidence-based digital engagement strategies demonstrate potential for redirecting dopamine-seeking behavior toward productive educational outcomes. The study concludes with a framework for "Positive Digital Engagement Design" (PDED) and recommendations for educators, technology designers, and policymakers seeking to balance engagement with educational integrity in the digital age.